Bending analysis of a sandwich plate with elliptical/circular cutout. Issue 1 (December 2020) - Lal, Achchhe; Sutaria, B.M; Kumar, Rahul
Abstract: Applications of sandwich plate as light weight structural member rapidly increased since last two decades because of its higher flexural rigidity to weight ratio. From aerospace vehicle to racing car, from giant submarine to small boat, from bicycle to high speed train all these weight sensitive areas have various parts made up by composite sandwich plates. Sometimes these members have hole of various shape for access of internal parts, lighting, ventilation etc. due to presence of these geometrical discontinuities in the form of hole, the structure gets more vulnerable to failure. During functioning, these parts usually acted upon by transverse force which may cause large deflection in the member or failure of the structure. Therefore, proper analysis of these structural member is desired for efficient and safe design. In the present work bending analysis of sandwich plate with elliptical and circular hole is carried out using finite element based first order shear deformation theory. A MATLAB program is developed for the present analysis. The efficiency of the program is found good as present results shows good agreements with the already published results.